ICampusGuide: a multi-purpose guide system in intelligent campus. (26th March 2020) - Yu, Chunyan; Qi, Hui; Chen, Haibao; Zhao, Shenghui; Wang, Sheng
As an important application of intelligent campus, campus guide aims to help visitors get to the destination. In this paper, a flexible and low-cost campus guide model named iCampusGuide is proposed, which generalises the problem of university campus guide including objectives, constraints, system and algorithms. The proposed iCampusGuide provides visiting reservation, route navigation, parking guideline and broadcasting introduction of buildings during the navigation. Technically, iCampusGuide adopts ibeacons for accurate locating and navigation, provides the parking suggestion by sending real-time snapshots from the parking lot nearest to the destination. Particularly, iCampusGuide provides business mode, tour mode, driving mode, walking mode for different purposes. Each mode uses different route navigation algorithms. To verify the model, a client-server software is developed and implemented in a real university campus. Experiments show that the model is effective.